2020
DOI: 10.1039/c9ra09136j
|View full text |Cite
|
Sign up to set email alerts
|

Excellent performance of aromatic polyguanamines induced by multiple hydrogen bondable tetraazacalix[2]arene[2]-triazine ring in their main chain

Abstract: Poly(guanamine)s containing tetraazacalix[2]arene[2]triazine ring within the polymer main-chain show outstanding thermal and mechanical properties arisen from the multiple-hydrogen bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The synthetic data and spectra of the compounds used in this study were described in a recently reported paper. 38 The formation of dichlorotetraazacalix [2]arene 2 triazine and the corresponding polymer can be seen in this paper. All compound data, including 1 H, 13 C, mass spectrometry (MS), elemental analysis, etc., including their purity, have been reported.…”
Section: ■ Experimental Sectionmentioning
confidence: 67%
See 1 more Smart Citation
“…The synthetic data and spectra of the compounds used in this study were described in a recently reported paper. 38 The formation of dichlorotetraazacalix [2]arene 2 triazine and the corresponding polymer can be seen in this paper. All compound data, including 1 H, 13 C, mass spectrometry (MS), elemental analysis, etc., including their purity, have been reported.…”
Section: ■ Experimental Sectionmentioning
confidence: 67%
“…The synthetic data and spectra of the compounds used in this study were described in a recently reported paper . The formation of dichlorotetraazacalix[2]­arene triazine and the corresponding polymer can be seen in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…PEG ( M n = 4600) end‐capped with NH 2 functions was prepared according to the previous report. [ 24 ] Figures S1 and S2 in the Supporting Information section show scheme of this synthetic protocol and 1 H NMR/GPC data, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, three different c‐PGs, each having the characteristic structural moiety which is comprised of two phenyl rings and two triazine rings alternately linked by amino groups and having a varying connecting moiety, are investigated. In the preparation of the c‐PGs [34] used in this study, cyanuric chloride and m ‐Phenylenediamine ( m PDA) were sequentially reacted at a molar ratio of 2 : 1 to synthesize the cyclic moiety as the first step. Then, 4,4’‐Oxydianiline (ODA), 9,9‐Bis(4‐aminophenyl)fluorene (BAFL), and m PDA were each reacted to produce the connecting moiety.…”
Section: Methodsmentioning
confidence: 99%
“…Newly synthesized polyguanamine derivatives having cyclic moieties (c‐PGs), [34] and their monolayer organization on the surface of an aqueous metal buffer demonstrated metal ion extraction from the subphase [35] . In the past 45 years, polyguanamine materials have attracted minimal attention [36] .…”
Section: Introductionmentioning
confidence: 99%